A history of interdisciplinary research on Lake Wigry - Aleksander-Kwaterczak, Urszula; Król, Katarzyna (Geology, Geophysics and Environment, 2021)
Lake Wigry is one of the best explored lakes in Poland, a feat which has been achieved thanks to the pas-sion and efforts of numerous scientists. This tremendous endeavour was supervised and coordinated by Professor Jacek Rutkowski and January 2021 marked the fifth anniversary of the professor’s death. To mark this occasion, a history of research on the lake was compiled on the basis of oral accounts and an overview of the works that have been created thanks to his ideas, supervision, and boundless empathy. It is crucial to continue the research, since it will allow for the even better protection of the environment, as well as the natural and landscape attributes of the Wigry region.